Pengaruh Pijat Kaki Terhadap Kualitas Tidur Pada Lansia Di Puskesmas Sering Kecamatan Medan Tembung Tahun 2023 - Lubis, Kristina; Adawiyah Harahap, Yuliatil; Agustian, Irwan; Sri Maharani Sitanggang, Fuji (Universitas Haji Sumatera Utara, 2025)
The high quality of sleep problems that occur in the elderly requires appropriate treatment to increase the fulfillment of sleep needs. Poor sleep quality can have an impact on the physical and psychosocial aspects of the elderly. Increasing the fulfillment of sleep quality needs can be done by teaching ways to stimulate and motivate sleep. One way that can be done is foot massage, a form of technique that involves moving the limbs. The purpose of this study was to analyze the effect of foot massage on sleep quality in the elderly. The quasi-experimental research design used the one group pretest and posttest only design approaches. The population of this study were 60 people. Sampling of this study using purposive sampling with a total of 30 people. Data processing editing, coding, scoring, and tabulating with Wilcoxon test analysis. The results of this study note that there are differences before and after being given education. Wilcoxon results in the study obtained a p value of 0.003 <0.05, meaning that there was an effect of foot massage on sleep quality in the elderly at the Frequent Health Center in Medan Tembung District in the intervention group, while a p value was obtained of 0.157> 0.05 meaning that there was no effect of foot massage on sleep quality in the elderly at the Sering District Health Center in Medan Tembung in the control group. The conclusion of this study, in the intervention group, namely that there was an effect of foot massage on sleep quality in the elderly at the Sering Community Health Center, Medan Tembung District, while in the control group, there was no effect of foot massage on sleep quality for the elderly at the Sering Public Health Center, Medan Tembung District. So it is hoped that the community will continue to apply regular foot massage activities for the elderly who experience poor sleep quality.